Європейський досвід підготовки вчителя фізичної культури до індивідуальної роботи з учнями - Мосейчук, Юрій; Цибанюк, Олександра (Науковий часопис Національного педагогічного університету імені М. П. Драгоманова, 2022)
В статті Ю. Мосейчука та О. Цибанюк «Європейський досвід підготовки вчителя фізичної культури до індивідуальної роботи з учнями» здійснено аналіз підготовки фахівців сфери фізичного виховання в різних країнах Європи. Автори виокремили спільні та загальні риси цього процесу, виділили проблеми та шляхи їх вирішення, зокрема в тому чи іншому закладі освіти. Так, в статті визнано, що крім основних завдань, що вирішуються на уроках фізичного виховання, учні знайомляться з навколишнім середовищем, природою, правилами соціальної поведінки, формуються уміння діяти в спільноті. Вирішення таких завдань досягається, зокрема через реалізацію міжпредметного та індивідуального підходів до уроків фізичної культури. Аналіз науково-методичної та спеціальної літератури з питання індивідуалізації процесу фізичного виховання школярів показав, що незважаючи на схожість поглядів багатьох учених на цю тему, врахування індивідуальних особливостей учнів у фізичному вихованні, далеко не завжди реалізується це в навчальному процесі.
European experience in training physical education teachers to work individually with students an analysis of the training of specialists in the field of physical education in different European countries. The authors singled out the common and general features of this process, identified problems and ways to solve them, in particular in a particular educational institution. The article proves that various aspects of the personnel problem are relevant also because the current requirements for the personality of a physical education teacher, the content of the subject, the attitude to it by teachers, parents, community, etc. are on time. Thus, the article recognizes that in addition to the main tasks to be solved in physical education lessons (promoting harmonious physical and mental development; meeting the needs of physical activity; general personality development; mastering popular sports, strengthening physical health, etc.), students get acquainted with the environment, nature, rules of social behavior, the ability to act in a community is formed. The solution of such tasks is achieved, in particular through the implementation of interdisciplinary and individual approaches to physical education lessons. Analysis of scientific and methodological and special literature on the individualization of the process of physical education of schoolchildren showed that despite the similarity of views of many scientists on this topic, taking into account the individual characteristics of students in physical education, it is not always realized in the educational process. It should be noted that there is another opinion on the individualization of school physical education.
Keywords: вчитель, досвід, заклади вищої освіти, підготовка фахівця, урок, фізична культура